(untitled) (Journal of the College of Basic Education, 2022)
In this paper, a new algorithm based on using Chebyshev waveletoperational matrix of integration instead of operational matrix of derivativeto find the approximate solution of two points boundary value problem.Wavelet first Chebyshev with aid of collocation method employed totransform the differential equation with its boundary condition to a systemof linear algebraic equations. A very high level of accuracy explicitlyreflected by the proposed examples.